Implementation of the Age Limitation for Marriage from the Perspective of Indonesian Family and Marriage Law - Wahyu Prabowo; Indira Swasti Gama Bhakti; Rr. Yunita Puspandari; Ivana Beatrice (Faculty of Law, Universitas Negeri Semarang, 2023)
The fundamental purpose of marriage is to unite couples as a family within a household. However, societal perceptions of marriage have evolved, particularly among the younger generation, resulting in instances of premarital pregnancies and engaging in dating and sexual activities that may contradict their religious beliefs. This increase in promiscuity has led to a surge in requests for marriage dispensation in courts to bypass the marriage age limit set by Indonesian Law Number 16 of 2019 on Marriage. To address this issue, this research employs a qualitative method to analyze data. The study findings reveal the need to amend Article 7, paragraph (1) of Law Number 1 of 1974 to Article 7, paragraph (1) of Law Number 16 of 2019 on Marriage. This amendment proposes raising the marriage age limit to 19 years old for both men and women, with the aim of ensuring the overall well-being and promoting the possibility of leading a respectable life. However, the implementation of the marriage age limit has not been fully effective due to the existence of Supreme Court Regulation No. 5 of 2019, which outlines guidelines for Marriage Dispensation Application Trials. This regulation weakens the age limitation legally, as judges refer to it when considering granting requests for marriage dispensation. In light of these circumstances, it is crucial for law enforcers and all stakeholders to prioritize the prevention of child marriage during the review process for marriage dispensation. This approach seeks to address the root causes of increasing promiscuity and premarital pregnancies, fostering an environment that encourages responsible and mature decision-making regarding marriage. Therefore, this study also emphasized that to ensure the general welfare of individuals and combat the rise in promiscuity and child marriage, amending marriage laws should be complemented with a focused effort on preventing child marriage during the dispensation process.